A facile approach to direct growth of layer-tunable graphene on Ge substrates. (November 2019) - Zhao, Yunbiao; Han, Dong; Wang, Xu; Hu, Zhaoyi; Chen, Yi; Chen, Yuhan; Zhou, Danqing; Li, Yue; Fu, E.G.; Zhao, Ziqiang
Abstract: Direct synthesis of graphene with tunable layer number on semiconductor has proven challenging. Synthesis of layer-tunable graphene on catalytic metal surfaces, in particular Cu and Ni, has shown great success. The growth methods on metal layers involve an inevitable transfer procedure, which degrades and contaminates the graphene. Thus, direct synthesis of graphene on semiconductor is necessary and profound. Here, a facile synthesis approach for direct growth of graphene on Ge(110) subtrate via ion implantation was reported. Interestingly, the graphene growth during annealing is not self-limiting and the thickness of graphene can be precisely controlled by the carbon ion implanted fluence. Moreover, a detailed growth process upon segregation was investigated, and the results show graphene nucleation tends to occur near the Ge atomic step edges. Furthermore, the facile approach involving the ion implantation can be adopted to investigate the growth process on semiconductor and to control the number of graphene layers, thus promoting the practical application of graphene in nanoelectronics. Graphical abstract: Image 1